Market Power, Types of Ownership and Bank Income Diversification: Cases of Asian Countries - Robertho, Valentino; Wibowo, Buddi (JDM (Jurnal Dinamika Manajemen), 2018)
This study aims to analyze the effects of market power and type of ownership on bank’s income diversification in Indonesia, Malaysia, the Philippines, Thailand, and China. Banks diversifies their source of income to stabilize profitability level. Bank’s market power is a critical factor which affect its income diversification efforts. This study uses Lerner Index as a proxy for banks’ market power. By using a sample of 80 banks in five countries from 2012 to 2016 and operating Fixed Effect Model and Generalized Least Square, the result shows that banks with greater market power earn more non-interest income, except in the Philippines. Also, government ownership is proven to heighten the relation between market power and income diversification, with consistent results shown in each subsamples. Foreign ownership also heighten the relation between market power and income diversification, except in Thailand.